Compilação dos cancioneiros galego-portugueses primitivos - B Penafiel, A (University of Santiago de Compostela, 2019)
Galician-Portuguese manuscript tradition is mainly composed of three exceptionally similar songbooks with regards to their selection and order of lyric texts. Based on these similarities, nineteenth-century scholars already posited lost manuscripts which could account for so many coincidences. Our understanding of the manuscripts’ genealogy improved substantially since the 1960s, when the relationship between the three main extant manuscripts was established in general terms. It has been enriched further in recent years with studies on codicology, graphematics and the structure of songbooks. This article focuses on medieval compilation as a complementary contribution to the on-going debate. Based on a codicological analysis of the Cancioneiro da Ajuda, it argues that the modus operandi of the team responsible for making the songbook varied. It then questions whether a compilator was part of this team and if his modus operandi also changed. The article then compares the contents of the Cancioneiro da Ajuda with those of the other two Italian songbooks, and connects variations in the texts with codicological variations. It argues that the Cancioneiro da Ajuda, its ancestor and the ancestor for the Italian manuscripts were not merely a sequence of copies, but actively compiled poetry from loose sheets, which caused substantial differences in the surviving manuscripts. The study establishes with greater precision the relationship between the three extant songbooks and points out that such relationship varies considerably depending on which specific poem is being compared